Identification of Immune-Related Key Genes as Potential Diagnostic Biomarkers of Sepsis in Children - Wang H; Huang J; Yi W; Li J; He N; Kang L; He Z; Chen C (Dove Medical Press, 2022)
Huabin Wang,1,2,* Junbin Huang,1,2,* Wenfang Yi,1,2,* Jiahong Li,3 Nannan He,4 Liangliang Kang,4 Zhijie He,5 Chun Chen1,2 1Division of Hematology/Oncology, Department of Pediatrics, the Seventh Affiliated Hospital of Sun Yat-Sen University, Shenzhen, 518107, People's Republic of China; 2Department of Pediatric Intensive Care Unit, the Seventh Affiliated Hospital of Sun Yat-Sen University, Shenzhen, 518107, People's Republic of China; 3Department of Neonatal Intensive Care Unit, the Seventh Affiliated Hospital of Sun Yat-Sen University, Shenzhen, 518107, People's Republic of China; 4Department of Pediatric Intensive Care Unit, Shenzhen Children's Hospital, Shenzhen, 518000, People's Republic of China; 5Department of Intensive Care Unit, Sun Yat-Sen Memorial Hospital of Sun Yat-Sen University, Guangzhou, 510000, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhijie He; Chun Chen, Email hezhijie@mail.sysu.edu.cn; chenchun69@126.comObjective: The pathogenesis of sepsis is still unclear due to its complexity, especially in children. This study aimed to analyse the immune microenvironment and regulatory networks related to sepsis in children at the molecular level and to identify key immune-related genes to provide a new basis for the early diagnosis of sepsis.Methods: The GSE145227 and GSE26440 datasets were downloaded from the Gene Expression Omnibus. The analyses included differentially expressed genes (DEGs), functional enrichment, immune cell infiltration, the competing endogenous RNA (ceRNA) interaction network, weighted gene coexpression network analysis (WGCNA), protein-protein interaction (PPI) network, key gene screening, correlation of sepsis molecular subtypes/immune infiltration with key gene expression, the diagnostic capabilities of key genes, and networks describing the interaction of key genes with transcription factors and small-molecule compounds. Finally, real-time quantitative PCR (RT-qPCR) was performed to verify the expression of key genes.Results: A total of 236 immune-related DEGs, most of which were enriched in immune-related biological functions, were found. Further analysis of immune cell infiltration showed that M0 macrophages and neutrophils infiltrated more in the sepsis group, while fewer activated memory CD4+ T cells, resting memory CD4+ T cells, and CD8+ T cells did. The interaction network of ceRNA was successfully constructed. Six key genes (FYN, FBL, ATM, WDR75, FOXO1 and ITK) were identified by WGCNA and PPI analysis. We found strong associations between key genes and constructed septic molecular subtypes or immune cell infiltration. Receiver operating characteristic analysis showed that the area under the curve values of the key genes for diagnosis were all greater than 0.84. Subsequently, we successfully constructed an interaction network of key genes and transcription factors/small-molecule compounds. Finally, the key genes in the samples were verified by RT-qPCR.Conclusion: Our results offer new insights into the pathogenesis of sepsis in children and provide new potential diagnostic biomarkers for the disease.Keywords: sepsis in children, key immune-related genes, transcriptomic analysis, Gene Expression Omnibus, diagnostic biomarkers